2012
DOI: 10.5424/sjar/2012102-495-11
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Isolation of Aeromonas hydrophila in piglets

Abstract: The production of Alentejano breed pig started a recovery two decades ago due to increasing demand for gourmet products. These pigs are raised in rotational semi-extensive or extensive outdoor production systems in the "Montado" (green and cork oak forest), grazing and feeding acorns and other associated food resources. Bacteria of the genus Aeromonas are considered as emerging pathogens of importance for man and animals, but its involvement in swine is not well documented. In the context of a study made at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…However, it is more often isolated from food of plant and animal origin than animal disease (Queiroga et al, 2012). A. hydrophila is producing haemolysins, enterotoxin (Ljungh et al, 1981) and is multidrug resistant (Queiroga et al, 2012), as it was observed here. Its isolation from pig gallbladders and its resistance to most of the antibiotics tested here, support its classification as an emerging pathogen for animals and man.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…However, it is more often isolated from food of plant and animal origin than animal disease (Queiroga et al, 2012). A. hydrophila is producing haemolysins, enterotoxin (Ljungh et al, 1981) and is multidrug resistant (Queiroga et al, 2012), as it was observed here. Its isolation from pig gallbladders and its resistance to most of the antibiotics tested here, support its classification as an emerging pathogen for animals and man.…”
supporting
confidence: 66%
“…hydrophila, incriminated in a variety of human clinical conditions, such as gastroenteritis, septicemia, cellulitis, myonecrosis, peritonitis, hepatitis, pancreatic abscesses, respiratory, urogenital and eye infections of immunocompromised individuals, is also implicated in infections of poikilothermic animals (amphibians, reptiles and fish) (Janda and Abbott, 2010). However, it is more often isolated from food of plant and animal origin than animal disease (Queiroga et al, 2012). A. hydrophila is producing haemolysins, enterotoxin (Ljungh et al, 1981) and is multidrug resistant (Queiroga et al, 2012), as it was observed here.…”
mentioning
confidence: 99%
“…Aeromonas hydrophila, a known zoonotic pathogen living mainly in water (Krovacek et al 1993;Rahimi-Larki and Nene 2006), has been associated with diseases in several fulminant fish and livestock (Pathiratne et al 1994;Rahimi-Larki and Nene 2006;Awaad et al 2011;Queiroga et al 2012), and caused severe losses in the aquaculture industry and animal husbandry. At present, antibiotics are the primary way to kill Aer.…”
Section: Introductionmentioning
confidence: 99%
“…They are also found in raw sewage, sewage effluents, and sewage-contaminated waters and activated sludge (Dumontet et al, 2001;Igbinosa et al, 2012). Aeromonads have long been considered as opportunistic pathogens of both aquatic (warmand cold-water fish) and terrestrial animals (Harikrishnan and Balasundaram, 2005;Isonhood and Drake, 2002;Queiroga et al, 2012). Nonetheless, the motile mesophilic aeromonads, and particularly Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue of major importance for the public health significance of Aeromonas spp. is the increasing documentation of isolates exhibiting resistance to several antimicrobial agents (Queiroga et al, 2012). Hence, in the context of basic control procedures common for all foodborne pathogens (i.e., prevention of contamination, reduction of contamination, and prevention of microbial growth), the aforementioned issues need to be particularly addressed with regard to aeromonads.…”
Section: Introductionmentioning
confidence: 99%